1971
DOI: 10.1139/m71-026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a canine adenovirus hemagglutinin

Abstract: MARUSYK, R. G., and T. YAMAMOTO. 1971. Characterization of a canine adenovirus hemagglutinin.Can. J. Microbial. 17: 151-155. The hemagglutinating activity of the canine adenoviruses was found to be more than 80y0 associated with both the intact and incomplete ('empty') virus particles, the remaining complete hemagglutinating activity being associated with a naturally occurring soluble penton dinier structure. Trypsin treatment of the heniagglutinin -red blood cell coniplex and receptor-competition experiments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Our data and numerous reports describing the ex vivo interaction of CAR-binding HAd5 with human/rat erythrocytes [12], [21]–[23], [29], [36], [51][53] strongly suggest this interaction probably occurs after the intravascular injection of CAR-tropic vectors. Notably, Lyons et al showed that that >90% HAd5 vector DNA was associated with blood cells following intratumoral injection during a clinical trial [34].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our data and numerous reports describing the ex vivo interaction of CAR-binding HAd5 with human/rat erythrocytes [12], [21]–[23], [29], [36], [51][53] strongly suggest this interaction probably occurs after the intravascular injection of CAR-tropic vectors. Notably, Lyons et al showed that that >90% HAd5 vector DNA was associated with blood cells following intratumoral injection during a clinical trial [34].…”
Section: Discussionsupporting
confidence: 77%
“…With respect to CAR affinity, the CAV-2 fiber head binds human CAR with the highest affinity of any fiber head known [24], which may favor its efficient hemagglutination. In contrast to other Ads, higher temperatures poorly inhibit CAV-2 hemagglutination [12], again suggesting a role for the high-affinity attachment to CAR. This is also consistent with a rather large difference between HAd5 and CAV-2 hemagglutination: to the best of our knowledge the HAd5 head does not harbor a sialic acid binding site and its pI (6.25) is less basic than HAd37 or CAV-2.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…14 Another canine adenovirus strain, serotype 1 (CAV-1), has also been partially characterized. Whereas, its cell entry biology has not been described to the extent that has been accomplished for CAV-2, the pathological, structural, biophysical, and serological dissimilarities of CAV1 [19][20][21][22][23][24] in comparison to CAV-2 suggest that a distinct underlying tropism may be operational. In light of these considerations, we explored the potential utilization of an adenoviral xenotype possessing the fiber-knob of CAV-1.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelial cells and hepatic and renal parenchymal cells are the main targets of CAV-1, while the respiratory tract epithelium and, to a limited degree, the intestinal epithelium, are the targets of CAV-2 [3,140,153]. In addition, the two types display different hemagglutination patterns [105].…”
Section: Canine Adenovirus Typementioning
confidence: 99%